Colaboração: 16 variações sobre um tema:: paradoxical configurations between dance, music and concept - Poppe, Maria Alice; Taborda, Tato (Revista Brasileira de Estudos da Presença, 2024)
The text investigates the interactions between dance and music in the piece Colaboração: 16 variações sobre um tema (Collaboration: 16 variations on a theme) by the dancer Maria Alice Poppe and the musician Tato Taborda. Its structure, a set of variations on a theme that reappears at the end, echoes Bach’s Goldberg Variations. Each of the variations refers to seminal themes, works and issues in contemporary dance and contemporary music, such as silence, noise, listening and body awareness, deepening the reflection on the interaction between sound and gesture, in the works and concepts of others artists, but also in works by the two artists, created over 10 years of artistic collaboration.